Hak Gugat Harta dalam Perkawinan Poligami - Deas Oktaviara Habiansyah; Dewi Astutty; M Ghufron Az; Mohammad Fahrial Amrullah (Bhirawa Law Journal, 2022)
As social beings, humans in living their daily lives are creatures who communicate with each other and need each other. It becomes a common thing when there is finally an attraction between the opposite sex. Love and affection are the reasons humans are bound in a relationship called marriage. Polygamous marriages cause several somah in marriage. Equality of position between husbands and wives will be determined by the pattern of marriage carried out. Based on legal facts, it is found that the husband's previous wife denied the rights. In addition, the rights to joint property are reduced by the interests of other wives, both second, third, and fourth. The type of research used by the author in this study is a type of normative legal research. If on one occasion another wife (second, third, and or fourth wife) in a marriage with the principle of polygamy commits fraud by using joint property unilaterally, then the first wife can sue civilly to the court against the unfair use of property, or it can go through the court of law. crime as a crime.